Effect of intracameral air injection during Ahmed glaucoma valve implantation on hypertensive phase - Kim, Sunghyun; Kwon, Yoonsung; Lee, Jong Yeon (Scientific reports, 2025)
The purpose of this study was to evaluate the difference in the incidence of the hypertensive phase (HP) between Ahmed glaucoma valve (AGV) patients who received intracameral air injection and those who did not. A total of 78 patients who underwent AGV surgery between January 1, 2016 and June 30, 2023 were included in this retrospective study. HP was defined as intraocular pressure (IOP) greater than 21 mmHg within the first 6 postoperative months. Among baseline characteristics, except for neovascular glaucoma and baseline IOP, there were no differences between the air injection and control groups. In the air injection group, the rate of HP was 19%, which was significantly lower than 49.1% in the control group ( p = 0.017). In multivariate logistic regression analysis, baseline IOP had a significant positive correlation (OR: 1.120, p = 0.026), while age and intracameral air injection had a significant negative correlation with the incidence of HP (OR: 0.938, p = 0.028, OR: 0.142, p = 0.029). Postoperative IOP at 1 year and surgical success rates were not different between the two groups. Intracameral air injection during AGV surgery can significantly reduce the risk of HP. Intracameral air injection can be a simple procedure in AGV surgery for reducing HP.